PTU-155 Investigation of the relationship between age, gender, body mass index (BMI) and bone mineral density (BMD) as assessed by dual-energy x-ray absorptiometry (DXA) of the spine and left femur in newly diagnosed patients with coeliac disease (CD). (22nd June 2015) - Pritchard, L; Lewis, SJ; Griffin, J; Pearce, G; Wilson, S
Abstract : Introduction: CD is a risk factor for osteoporosis and low BMD (osteopenia). Present national guidelines (BSG 2007) do not identify young patients with CD as being at risk of low BMD. Few studies have investigated BMD in coeliac patients below 40 years of age. This audit analysed the DXA results of newly diagnosed coeliac patients attending a coeliac clinic. Method: BMD (age matched Z-scores) as assessed by DXA in consecutive patients with CD between 2013 and 2014 were compared for age, gender and BMI (majority ≤12 months of diagnosis). Low BMD was defined locally as: Z-score -1.5. This compares to WHO criteria for osteopenia: T-score of <-1 and >-2.5 and osteoporosis: T-score of ≤-2.5. Results: Conclusion: Current UK guidelines (BSG 2007) recommend that BMD should be measured in coeliac patients after 1 year of a gluten-free diet (GFD) in patients who have additional risk factors for osteoporosis or if over 55 years. We found 28% of patients < 55 years had osteopenia and 5% had osteoporosis. Males were more likely to have osteopenia vs. females, 42% vs. 26%. The prevalence of osteoporosis increased with age. Those with normal BMI were more likely to have osteopenia (45%). No obese patients scanned had osteoporosis. The risk of osteoporosis and bone fracture is increased with CD and adherence to a GFD may only partially improve BMD. More research is needed to explore the effect of the GFD on bone health over time and the optimal time to perform DXA scanning. Patients once stabilised on a GFD are usually discharged back into the community with no routine hospital follow up. Subsequently, opportunities for detection of suboptimal bone health may be missed. Consideration should be given to perform DXA in patients diagnosed with CD below the age of 55 years. Disclosure of interest: None Declared. Reference: British Society of Gastroenterology (BSG). Guidelines for osteoporosis in inflammatory bowel disease and coeliac disease, 2007